Status of northern white rhinos and elephants in Garamba National Park, Democratic Republic of Congo, during the wars - Hillman, Smith (Pachyderm, 2001)
In recent years meat has been the premis behind poaching in Garamba NP. Patrol records suggest 70-80% of the poachers are Sudanese, often SPLA deserters, and the rest are Congolese. The significant increase in poaching in 1997 during the first DRC war was related to the fact that the guards were disarmed by occupying military forces and so had no control over poaching. There was no increase during the second DRC war, 1999-2000, although the Park headquarters was occupied by Ugandan-backed rebel forces, the personnel were not disarmed and there was little disruption to their anti-poaching efforts. Aerial survey counts in 1995 estimated 11,175 elephant. In May-June 1998, the estimated population was 5874, and in 2000 it was 6022. Observations suggest one half the elephants were lost during the first war, but there was no significant loss during the initial phase of the second war. Recent genetic results illustrate what observers have long suggested: Garamba elephants appear morphologially and behaviourly to be an intergrade between forest elephant (Loxodonta africana cyclotis) and savannah elephant (Loxodonta africana africana). International assistance focused on Garamba is noted.